Hubungan Dukungan Keluarga Dengan Motivasi Pasien Hipertensi Dalam Memeriksakan Tekanan Darah Di Puskesmas Belimbing Padang Tahun 2025 - Ayu Tania Putri (CV. ITTC INDONESIA, 2026)
The incidence of hypertension in the carambola Health Center in 2024 is 8000 cases. The incidence of hypertension in Puskesmas Belimbing in the last three months as many as 761 cases with hypertension patients at the age of 25-59 years as many as 200 people. Many people with hypertension currently do not control blood pressure to health facilities, because there is no support from the family in responding to the patient's need to run an examination. The purpose of this study was to determine the relationship of family support with the motivation of hypertensive patients in checking blood pressure in Puskesmas Belimbing Padang. This type of research is descriptive analytic with cross sectional study. This research was conducted at Puskesmas Belimbing Padang. Research time is in January to August 2025. Data collection was carried out in August 2025. The population in this study were all hypertensive patients in Puskesmas Belimbing Padang in the last three months as many as 200 people with a sample of 67 people. Sampling technique is accidental sampling. Data analysis using statistical analysis of Chi-Square test results. The results showed that 53.7% of respondents had poor motivation and 55.2% of respondents had poor family support. There is a relationship between family support and the motivation of hypertensive patients in checking blood pressure at the Belimbing Padang Health Center in 2025 with a p-value= 0.000. There is a significant relationship between family support with the motivation of hypertensive patients in checking blood pressure. Through the leadership of Puskesmas Belimbing, the results of this study are expected to be used as input for health workers in preventing complications of hypertension through counseling on motivation to check blood pressure in hypertensive patients.